Genetics of gonadotropins and their receptors as markers of ovarian reserve and response in controlled ovarian stimulation. (October 2017) - Riccetti, Laura; De Pascali, Francesco; Gilioli, Lisa; Santi, Daniele; Brigante, Giulia; Simoni, Manuela; Casarini, Livio
Abstract : Several controlled ovarian stimulation (COS) protocols have been developed to increase the yield of mature oocytes retrieved in assisted reproductive techniques (ARTs). The ovarian reserve (OR) influences the COS response, and it represents the main parameter that helps clinicians in refining clinical treatments in the perspective of a "personalized" ART. This approach is even more needed in particular conditions such as poor OR or polycystic ovary syndrome. Follicle-stimulating hormone, luteinizing hormone, and human chorionic gonadotropin are currently used in COS at different combinations and with different efficacies, even if the best approach definition is controversial. Differences in individual-specific ovarian response to gonadotropin stimulation can be due to alterations of genes encoding for hormones or their receptors. In particular, FSHB c.-211G>T, FSHR p.Asn680Ser, and c.-29G>A SNP allelic combinations may be used as OR and COS response markers. The purpose of this review is to highlight the evidence-based relevance of mutations and polymorphisms in gonadotropins and their receptor genes as predictive markers of OR and COS response to achieve fine-tuned therapeutic regimens. Highlights: FSHB c.-211G>T, FSHR p.Asn680Ser, and c.-29G>A SNPs are OR and COS response markers. No solid association between LHCGR/LHB SNPs and OR or COS response is determined. FSHR / FSHB allelic combinations may inform the effect of genetic variants on COS.